Ради молодих вчених України: 2022. Незламні - (:unkn) unknown (My University, 2023)
Наведено узагальнену інформацію про діяльність Рад молодих вчених у закладах вищої освіти та наукових установах України. Сучасний стан та перспективи активності наукової молоді подано для інформування громадськості про самоорганізаційний потенціал молодих науковців та обмін кращими практиками популяризації науки та підтримки громадських ініціатив дослідників. General information is provided on the activities of the Councils of Young Scientists in higher education institutions and scientific institutions of Ukraine. The current state and prospects of the activity of young scientists are presented to inform the public about the self-organizational potential of young scientists and exchange best practices in popularizing science and supporting public initiatives of researchers.
Keywords: Рада молодих вчених; Council of Young Scientists; заклад вищої освіти; institution of higher education; молодь; young; молодіжна наука; youth science